2021
DOI: 10.1002/adom.202100135
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Responsive Circularly Polarized Luminescence Polymers with INHIBIT Logic Function

Abstract: Dynamically tuning the emission of circularly polarized luminescence (CPL) materials through external stimuli is fascinating because of their fundamental and application interests. In this work, light‐responsive and luminescence‐tunable CPL‐active materials are synthesized by mixing achiral helical polymer containing vibration‐induced emission (VIE) molecules and spiropyran (SP) with a chiral helical polymer. Through regulating the distinct emission of VIE molecules and the reversible photoisomerization of SP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 49 publications
(11 reference statements)
0
18
0
Order By: Relevance
“…[ [164][165][166] and Ma et al [167] have further demonstrated the "Matching Rule" is potentially applicable to numerous chiral matters and achiral fluorophores, clearly confirming the wide universality and superiority of the strategy. Although striking advancements have been and are being achieved continuously, the development of polymer-based CPL materials is still at the infant state.…”
Section: Constructing Cpl-active Polymers Via Physically Blendingmentioning
confidence: 89%
“…[ [164][165][166] and Ma et al [167] have further demonstrated the "Matching Rule" is potentially applicable to numerous chiral matters and achiral fluorophores, clearly confirming the wide universality and superiority of the strategy. Although striking advancements have been and are being achieved continuously, the development of polymer-based CPL materials is still at the infant state.…”
Section: Constructing Cpl-active Polymers Via Physically Blendingmentioning
confidence: 89%
“…In addition, the photochromic compounds also should have good photostability, wide spectral shift between different states, and a high extinction coefficient. Thus, naphthopyran (NP) was chosen in this work instead of azobenzene, , spiropyran, , and dithienylethene. , In 2017, Inagaki et al reported the NP derivatives with simple synthesis and superior photochromic performance. To ensure a good spectral overlap with common fluorescent dyes emitting in the visible range, we synthesized NP1, NP2, and NP3 (Figure b) by introducing electron-donating groups (methoxy and piperidino groups) to red-shift the absorbance (see Figures S1–S9 for NMR and MS characterizations) .…”
Section: Resultsmentioning
confidence: 99%
“…Ma et al reported a photoactive achiral copolymer (Figure 1a) modified with spiropyrans. [23] Spiropyran units (SPCH) and vibration-induced emissive units (DPCH) were both introduced into the achiral polymer to achieve multicolor fluorescence through Förster resonance energy transfer (FRET). Surprisingly, before UV irradiation, no FRET was detected between DPCH and SPCH.…”
Section: Spiropyran-based Light-responsive Supramolecular Cpl Materialsmentioning
confidence: 99%